VAGINOSCOPIC DETERMINATION OF OVUL TION AND FERTILE BREEDING TIME TO OPTIMIZE CONCEPTION IN BITCHES - SRIDEVI, P; VEERAPANDIAN, C; SUBRAMANIAN, A (The Indian Journal of Animal Reproduction, 2011)
Twenty sub fertile bitches of different breeds at day 1 of proestrual bleeding were subjected to vaginoscopy and LH estimation to predict the time of ovulation and fertile breeding time. Based on vaginoscopic assessment of vaginal mucosa, the mean length of shrinkage period without angulation corresponding to the period of LH surge and ovulation was 5.45 ± 0.21 days while, the mean length of the angulated shrinkage period corresponding to fertilization period was 5.00 ± 0.35 days. The LH surge occurred on an average 9.95 ± 0.67 days from day 1 of proestrual bleeding and the calculated time of ovulation (LH surge+ 48 h) was 11.95 ± 0.67 days from the onset of proestrual bleeding and ranged from 9 to 20 of the cycle. A high co-efficient of correlation (P < 0.01) of 0.96 was observed between LH and vaginoscopy.